2013
DOI: 10.1063/1.4820414
|View full text |Cite
|
Sign up to set email alerts
|

Human red blood cell behavior under homogeneous extensional flow in a hyperbolic-shaped microchannel

Abstract: It is well known that certain pathological conditions result in a decrease of red blood cells (RBCs) deformability and subsequently can significantly alter the blood flow in microcirculation, which may block capillaries and cause ischemia in the tissues. Microfluidic systems able to obtain reliable quantitative measurements of RBC deformability hold the key to understand and diagnose RBC related diseases. In this work, a microfluidic system composed of a microchannel with a hyperbolic-shaped contraction follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
90
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(108 citation statements)
references
References 34 publications
8
90
0
Order By: Relevance
“…Experiments with different flow rates (5 and 15 μL/min) were also performed. The results corroborate with past studies 6,11 were they found that flow rate has a weak effect on the downstream CFL. Additionally, Figure 4 shows that the highest CFLs thickness occur at microchannels with a εH of 3.6 and 4.2.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Experiments with different flow rates (5 and 15 μL/min) were also performed. The results corroborate with past studies 6,11 were they found that flow rate has a weak effect on the downstream CFL. Additionally, Figure 4 shows that the highest CFLs thickness occur at microchannels with a εH of 3.6 and 4.2.…”
Section: Resultssupporting
confidence: 83%
“…The present results corroborate the study performed by Yaginuma et al (2013) 11 , where by using a single hyperbolic contraction with a εH = 3, they have showed that for this particular hyperbolic contraction the downstream CFL enhanced by nearly ten times relatively to the CFL upstream of contraction region.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…To address these issues, microfluidic tools have recently been explored as a strategy to measure cellular structural and mechanical properties with a rapidity that may be better suited to drug discovery and clinical application (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Although these approaches have indeed massively improved measurement throughput and reduced operator skill/bias issues relative to traditional measurements, the extraction of cell mechanical properties (e.g., elastic modulus) remains challenging, primarily due to complex viscous forces that severely complicate analysis of deformations.…”
Section: Introductionmentioning
confidence: 99%